Exchange Rate Uncertainty Effect on Export-Oriented Companies at Tehran Stock Exchange (yield) Rate of Return: A Panel- Vector Autoregressive Model - Zamanian, Gholamreza; Mahmodpour, Kamran; Yari, Sepideh (International Journal of Economics and Financial Issues, 2017)
The main purpose followed in this research is to analyze effect of exchange rate uncertainty on the export-oriented companies' rate of return at Tehran Stock Exchange applying Panel-vector autoregressive model during 2004-2014. The results indicate that the companies' rate of return is affecting by factors such as (exchange rate uncertainty, profitability index, size of company, debt ratio, book value to market value of each stock ratio).In accordance with the results, the return's response to leverage index (debt ratio) is consistently negative while the return's responses to profitability index and the book value to market value are positive at first and then turn negative. In addition, the size of company initially affects the rate of return negatively and then has an insignificant positive effect on it, which means the greater the company is, the more rate of return it has in long term. Consequently, it is indicated that the effect of exchange rate's uncertainty on export-oriented companies 'rate of return is positive in both short and long run; which presents that the more exchange rate uncertainty is, the more rate of return we will have in long run. Keywords: Exchange Rate, Tehran Stock Exchange, Panel Vector Autoregressive Model JEL Classifications: F31, G2